Gel Formation Mechanism of κ-Carrageenan in Co-solute Field and Its Application in 3D Printing - Meirong RUAN; Zhenbin LIU; Siyu HA; Yucheng ZENG; Yanhua TANG; Hongbo LI; Liangbin HU; Haizhen MO (Shipin gongye ke-ji)
κ-Carrageenan is widely used in the food industry due to its excellent gelling ability. The co-solute field refers to the environment in which the sol-gel transformation of polymer materials, such as proteins or polysaccharides, occurs. This environment is not a simple aqueous solution containing only polymer components, it also includes one or more small molecule co-solutes such as sucrose, emulsifiers, and polyols. Co-solutes significantly impact the gelation process of κ-carrageenan. Three main hypotheses explain this mechanism: The ''structure of water" effect induced by co-solutes, the "expulsion effect" of polymers on co-solutes, and the "binding effect" between co-solutes and polymers. However, there is no unified conclusion yet. Additionally, this article reviews the application of κ-carrageenan in 3D printed food, including its use as a gel matrix material for 3D printing and as an additive to regulate the 3D printing characteristics of different food systems.